Assessment of Mine Plans for Production and Variations at Ibese Limestone Mines - AFENI, Thomas Busuyi; ADEYEMI , Adedapo Jacob; MOHAMMED, Kolawole Tajudeen (ABUAD Journal of Engineering and Applied Sciences, 2024)
This research investigated the mine plans used for the production target and annual production of limestone for the past seven (7) years. The actual amount of limestone produced per year in tons was computed to determine the variations in the mine’s production and the life span of the reserve of limestone deposits. A new mine plan was proposed, and a targeted amount of limestone production per year was suggested. The mine plans for the mine’s production were generated from 2014 to 2020 using a complete data collection system for Real Time (RTK) GPS and Total Stations with in-field coordinate geometry called SurCE by Carlson Software. The total production target for the seven (7) years was 87,017,146 tons and the actual production was 76,313,056 tons. The total variations for the years under this assessment were -10,704,090 tons except for the year 2018 when the actual production was higher than the production target of 511,179 tons. The volumetric reserve estimation revealed that the total volume of the limestone reserve is 5,052,236,090.186 tons. The expected production per week was computed to be 356,400 tons/week, expected monthly production, (EMP) was estimated to be 1,425,600 tons/month. The expected production year, (EPY) was 17,107,200 tons/year and the life span of the limestone deposit, (LS) was computed to be 295.34 years. It can be suggested that the company should target a production rate of 1,425,200 monthly and 17,104,200 per year. This suggestion can be achieved if there is enough investment in terms of skilled labour, heavy-duty machinery, and equipment which will cost-effectively boost production.